Dissecting the differential performance of contrasting stay-green and stem reserve mobilization wheat (Triticum aestivum L.) genotypes – Validation of GWAS analysis - Animireddy China Malakondaiah; Ajay Arora; Hari Krishna; Sukumar Taria; Sudhir Kumar; Sekar Kousalya; Narayana Bhat Devate; Jasdeep Chatrath Padaria; Sahana Police Patil; Pradeep Kumar Singh (PLoS ONE, 2026)
The present study aimed to validate the identified marker trait associations (MTAs) for stay-green (SG) and stem reserve mobilisation (SRM) using 12 wheat genotypes. Out of 12 genotypes, equal number of genotypes (6 each) had higher and lower SG and SRM traits. These genotypes were selected from our previous genome-wide association study for SG and SRM traits. Validation of mapped MTAs have been accomplished by using physiological and gene expression approach. Gene expression analysis of the identified genes in the MTAs region were carried out in these selected contrasting lines in a pot experiment site at Division of Plant Physiology, Indian Agricultural Research Institute (IARI), New Delhi, India. For SG traits, canopy temperature (CT), soil plant analysis development (SPAD) value, leaf senescence rate (LSR) was recorded, whereas for SRM, stem reserve mobilisation efficiency (SRE) was measured. The experiment was carried out in completely randomized design (CRD), under control and combined heat and drought stress (HD) condition. Plants in the control condition (timely sown) were irrigated at their critical phenological stages throughout the cropping period, while under combined stress (50 days late sown), irrigation was withheld at the flowering stage to impose drought stress. Candidate genes found in the overlapping region and within the region of 100 Kb intervals flanking either side of the associated markers were identified through BioMart tool in Ensemble Plants platform. Real-time gene expression analysis was performed on SG-associated genes in the flag leaf and SRM- associated genes in the peduncle. Phenotypic assessment showed that there was significant genotypic variation for the SG and SRM traits and yield. Low SG and SRM performing genotypes showed around 27% and 37% faster leaf senescence rate (LSR) than high SG and SRM performing genotypes under control and HD conditions, respectively, which confirming to our mapped MTAs for SG and SRM traits. HD3366 showed highest stem reserve mobilisation efficiency (SRE) of around 85% under combined stress, while lowest of around 27% was recorded in MP1369 under control condition. Thousand grain weight (TGW) showed negative association with LSR, while positive correlation with SRE. However, highest relative gene expression of cytokinin dehydrogenase 11-like ( TaCKX11 ) was recorded in low performing SG and SRM genotypes, while lowest expression was recorded in high performing SG and SRM genotypes. Expression analysis of candidate genes like protein phosphatase 2C ( TaPP2C ), TaCKX11 , protein detoxification 40-like ( TaPD ), F-box protein ( TaFBP ) and pentatricopeptide repeat ( TaPPR ) were associated with leaf senescence (SG- linked). Genes linked with SRE, such as serine/threonine-protein kinase 2 ( TaSK2 ) and wall-associated receptor kinase 4- like ( TaWAK ) exhibited the highest expression levels during 12 days after anthesis, suggesting their involvement in enhanced carbon reserve mobilization to the grain under stress conditions. Our study confirmed the association of mapped markers and its linked traits, which can be used in further marker-assisted selection (MAS) using efficient breeding tools.